Особливості реалізації адміністративно-правових норм у діяльності Національної поліції України - Невядовський, В. О.; Neviadovskyi, V. O.; ORCID: http://orcid.org/0000-0002-3107-1464 (Вісник Харківського національного університету внутрішніх справ. - 2016. - № 4 (75). - С. 170-176, 2016)
З урахуванням позицій учених-адміністративістів крізь призму національного правового поля окреслено основні особливості реалізації адміністративноправових норм у діяльності Національної поліції України. Зроблено висновок про недостатній рівень висвітлення на сторінках правової літератури результатів дослідження особливостей діяльності Національної поліції України з урахуванням досвіду роботи вказаного правоохоронного органу. Запропоновано особливості реалізації адміністративно-правових норм у діяльності Національної поліції України поділити на дві групи – теоретико-правові та організаційні.

Among the reasons for the inhibition of any reform of the political, social, economic or legal nature the author has singled out public reluctance to accept innovations, the lack of political will, the inadequacy of the current legal base to the real requirements of the reform. The relevance of chosen research topic has been grounded by the lack of sufficient number of research focused on the activities of one of the key law enforcement agencies – the National Police of Ukraine on the pages of legal literature. Taking into account the points of view of scholars in administrative law in the light of the national legal framework, the author has outlined the main features of implementing administrative and legal norms within the activities of the National Police. The author includes the following main features: the use of the terms that did not find its consolidation, in particular “public security” and “public order” by the legislator; the need to provide details of the provisions of certain Articles of the Code of Ukraine on Administrative Offenses, in particular the Art. 222 on the powers of the National Police agencies in regard to cases of administrative offenses. Special attention has been paid to the need to address the legal shortcomings of the current legislation in order to have a clear understanding by the police officers of the assigned tasks and the scope of own powers and jurisdiction in reviewing the materials on administrative proceedings. The peculiarities of the structure of some Articles of the Code of Ukraine on Administrative Offenses, in particular the Articles 154 and 160. The author has offered solutions to the determined legal conflicts in carrying out the proceedings under the stated Articles. The author has suggested to divide the features of implementing administrative and legal norms within the activities of the National Police into two groups – organizational and theoretical and legal.

С учётом позиций учёных-административистов сквозь призму национального правового поля обозначены основные особенности реализации административно-правовых норм в деятельности Национальной полиции Украины. Сделан вывод о недостаточном уровне освещения на страницах юридической литературы результатов исследования особенностей деятельности Национальной полиции с учётом опыта работы указанного правоохранительного органа. Предложено особенности реализации административно-правовых норм в деятельности Национальной полиции Украины разделить на две группы – теоретико-правовые и организационные.
Особенности реализации административноправовых норм в деятельности Национальной полиции Украины
Features of implementing administrative and legal norms within the activities of the National Police of Ukraine
Невядовський, В. О. Особливості реалізації адміністративно-правових норм у діяльності Національної поліції України / В. О. Невядовський // Вісник Харківського національного університету внутрішніх справ. - 2016. - № 4 (75). - С. 170-176.
Невядовський В. О. "Особливості реалізації адміністративно-правових норм у діяльності Національної поліції України." Вісник Харківського національного університету внутрішніх справ 4 (2016): 170-176.
Neviadovskyi, V.O. (2016), “Features of implementing administrative and legal norms within the activities of the National Police of Ukraine” [Osoblyvosti realizatsii administratyvno-pravovykh norm u diialnosti Natsionalnoi politsii Ukrainy], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 4, pp. 170–176.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Національна поліція України. National police of Ukraine. Национальная полиция Украины; поліція; правоохоронна діяльність; правоохоронні органи; адміністративно-правова норма; правова колізія; National police of Ukraine; law enforcement activity; law enforcement agencies; administrative and legal norm; legal conflict; Национальная полиция Украины; полиция; police; правоохранительная деятельность; правоохранительные органы; административно-правовая норма; правовая коллизия